Stereoselective synthesis of novel C-3 functionalized 3-sulfonyl-β-lactams: Promising biologically active heterocyclic scaffolds. Issue 12 (22nd March 2017) - Bhalla, Aman; Modi, Garima; Bari, Shamsher S.; Kumari, Anu; Berry, Shiwani; Hundal, Geeta
Graphical abstract: Highlights: Stereoselective synthesis of novel C -3 functionalized 3-sulfonyl-β-lactams. Simple, efficient and fast (30 min–4 h) strategy for mild C -3 functionalization via Michael addition. Exploration of steric bulk and chirality of Michael acceptor on C -3 functionalization. Stereochemistry at C -3 of 3-functionalized sulfonyl β-lactams3e was established by X-ray structural analysis. C -3 functionalized β-lactams: potential synthons and promising biologically active heterocyclic scaffolds. Abstract: An efficient and operationally simple strategy for the stereoselective synthesis of novel C -3 functionalized 3-sulfonyl-β-lactam heterocycles is described. The C -3 functionalized 3-phenyl/benzylsulfonyl-β-lactams3/3′, 5/5′ has been synthesized via Michael addition using different Michael acceptors on trans -3-phenyl/benzylsulfonyl-β-lactams2(a–f) using K2 CO3 as a base and acetonitrile/DMF as solvents. The reaction furnished exclusively cis- β-lactam adducts3(a–r) using sterically less hindered Michael acceptors. Further, the effect of steric bulk and chiralilty of Michael acceptors was explored to achieve target C -3 functionalized β-lactams3(s-u)/3′(s-u) and5(a–c)/5′(a–c) . The structural and stereochemical analysis of novel β-lactams were carried out using FT-IR, NMR ( 1 H, 13 C, 1 H- 1 H COSY, 1 H- 13 C COSY and 13 C DEPT-135), elemental analysis (CHNS), mass spectrometry (EIMS and LCMS) in representative cases and single crystal X-ray crystallographic studies (3e ). The cis or trans configuration of the Michael acceptor (E) at C-3 was assigned with respect to C4-H.